Resistive switching in sub-micrometric ZnO polycrystalline films. (13th December 2018) - Conti, D; Laurenti, M; Porro, S; Giovinazzo, C; Bianco, S; Fra, V; Chiolerio, A; Pirri, C F; Milano, G; Ricciardi, C
Abstract: Resistive switching (RS) devices are considered as the most promising alternative to conventional random access memories. They interestingly offer effective properties in terms of device scalability, low power-consumption, fast read/write operations, high endurance and state retention. Moreover, neuromorphic circuits and synapse-like devices are envisaged with RS modeled as memristors, opening the route toward beyond-Von Neumann computing architectures and intelligent systems. This work investigates how the RS properties of zinc oxide thin films are related to both sputtering deposition process and device configuration, i.e. valence change memory and electrochemical metallization memory (ECM). Different devices, with an oxide thickness ranging from 50–250 nm, are fabricated and deeply characterized. The electrical characterization evidences that, differently from typical nanoscale amorphous oxides employed for resistive RAMs (HfO x, WO x, etc), sub-micrometric thicknesses of polycrystalline ZnO layers with ECM configuration are needed to achieve the most reliable devices. The obtained results are deeply discussed, correlating the RS mechanism to material nanostructure.